Performance Analysis of Python Based SDN Controllers over Real Internet Topology - Chandroth, Jisi; Roh, Byeong Hee; Ali, Jehad (International Conference on Ubiquitous and Future Networks, ICUFN, 2022)
SDN (Software-Defined Networking) is a revolutionary networking paradigm that separates the data plane and control plane to allow for intelligent network operation. Traffic management, routing, security, and analysis are all responsibilities performed by the control plane. The controller, which offers information to the whole network, is a critical component of the control plane. SDN controllers such as POX, Ryu, Open Daylight, Beacon, and ONOS are frequently utilized. These controllers' behavior is determined by the installed environment, network architecture, and kind of traffic flow, among other factors. It's crucial to compare these controllers in order to learn more about their capabilities. The performance of python-based controllers in Abilene topology is evaluated in this research. Moreover, we also perform a comparison with an increase in the number of nodes. The results of the testing demonstrate that Ryu performs better than POX.
Keywords: Control planes; Data control; Data planes; Data-plane; Internet topologies; Network operations; Performances analysis; POX; RYU; Software-defined networkings; POX; RYU; SDN